Maternal night-eating pattern and glucose tolerance during pregnancy : study protocol for a longitudinal study - Loy, See Ling (2020)
Introduction: Coordinating eating schedules with day–night cycles has been shown to improve glucose regulation in adults, but its association with gestational glycaemia is less clear. A better understanding on how eating time can influence glucose levels in pregnancy may improve strategies for gestational glycaemic control. This study aims to examine the association of maternal night-eating pattern with glucose tolerance in the second trimester of pregnancy, and to investigate how lifestyle factors may be related to night-eating pattern. Methods and analysis: This is an observational longitudinal study that targets to recruit 200 pregnant women at 18–24 weeks’ gestation from the KK Women’s and Children’s Hospital in Singapore. Data collection includes sociodemographics, lifestyle habits and obstetric information. Maternal dietary intake is collected using the 4-day food diary and food frequency questionnaire; while 24-hour physical activity, sedentary behaviour, sleep and light exposure are captured using the accelerometer at 18–24 weeks’ gestation. Continuous glucose monitoring at 18–24 weeks’ gestation, oral glucose tolerance test and insulin test at 24–28 weeks’ gestation are performed to assess glycaemic outcomes. Multivariable generalised linear models will be used to analyse the association of maternal night-eating pattern (consumption of meal and snack during 1900–0659 hours) with glycaemic measures, and the associated factors of night-eating pattern, controlling for potential confounders. Recruitment began in March 2019 and is estimated to end in November 2020. Ethics and dissemination: Ethical approval has been granted by the Centralised Institutional Review Board of SingHealth, Singapore (reference 2018/2529). The results will be presented at conferences and disseminated in journal articles.